Sufism in Ottoman Egypt: circulation, renewal and authority in the seventeenth and eighteenth centuries - Chih, Rachida (Routledge Sufi series, 2019)
Circulation and networks: the role of Cairo and al-Azhar -- Education : how to guide disciples? -- The Muhammadan path (Tariqa Muhammadiyya) and Sufi renewal -- Prophetic heritage, authority and the intercession of saints.